ESMO Updates the Guidelines for the Diagnosis of *RET*-Altered Cancer to Herald a New Era in Targeted Therapy - Alfredo Addeo; Frank Stenner (healthbook TIMES. Oncology Hematology)
The *RET* gene encodes a tyrosine kinase receptor that regulates cell survival and proliferation by triggering key downstream pathways.^1^ *RET* gene mutations and *RET* gene fusions are involved in the pathogenesis of lung, thyroid and other cancers. Recently, in 2021, the European Society for Medical Oncology (ESMO) has developed recommendations for the laboratory diagnosis of targetable *RET* rearrangements and mutations.^2^ Following the results from phase I/II clinical trials,^3,4^ selpercatinib, a RET tyrosine kinase inhibitor (TKI), received the FDA^5^ and Swissmedic^6^ authorization for the treatment of adult patients with *RET* fusion-positive non-small cell lung cancer (NSCLC) and advanced *RET* fusion-positive thyroid cancer who require systemic therapy and who have progressed after prior treatment. Selpercatinib is also indicated for the treatment of adults and adolescents ≥12 years old with advanced *RET*-mutated medullary thyroid carcinoma (MTC) who require systemic therapy and who have experienced progression after prior treatment with TKIs. In this clinical setting, the Food and Drug Administration (FDA) has recently approved another RET TKI, pralsetinib.^7^ In addition, the FDA also granted accelerated approval to pralsetinib for adult patients with metastatic *RET* fusion-positive NSCLC.^8^ This review aims to summarize the new ESMO recommendations for the laboratory diagnosis of *RET*-altered cancers and the clinical trial data that support the regulatory approvals of selpercatinib and pralsetinib for *RET*-altered NSCLC and thyroid cancer.